Analisis Implementasi Penyuluh Kehutanan Terhadap Kelola Usaha Pada Kelompok Tani Hutan Di Tahura Nuraksa : Analysis of the Implementation of Forestry Extension on Business Management in Forest Farmer Groups at Tahura Nuraksa - Maulida, Arifa Yunia; Ichsan, Andi Chairil; Aji, Irwan Mahakam Lesmono (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
There is only one Taman Hutan Raya (Tahura) located in West Nusa Tenggara province, Tahura Nuraksa with the administrative division of the area located in West Lombok regency and Central Lombok regency. The total area of Tahura Nuraksa is 3.155 ha. It is divided into six blocks, one of which is a traditional block used for plantation activities by the community. There are 14 Forest farmer groups (KHT) assisted by Tahura Nuraksa extension officers with beginner and intermediate class levels. This study aims to determine the process of implementation of the tasks and functions of Tahura Nuraksa forestry extension on forest farming group business management with descriptive methods using quantitative and qualitative approaches. Sample determination using purposive sampling method by selecting 42 respondents consisting of chairman, treasurer and Secretary of the 14th KTH. The research results were processed using SWOT analysis.